Semantic challenges to realism : Dummett and Putnam - Gardiner, Mark Q. (Mark Quentin), 1963- (Toronto studies in philosophy., 2000)
Although many philosophers espouse anti-realism, the only sustained arguments for the position are due to Michael Dummett and Hilary Putnam. Gardiner's unpretentious style and lucid organization make sense of Dummett's and Putnam's discourse.